Gugat Cerai Karena Suami Tidak Memberi Nafkah Menurut Undang-Undang Perkawinan dan Hukum Islam - Riski Marito Daulay (Tabayyanu : Journal Of Islamic Law, 2024)
This study examines divorce lawsuits filed by wives due to the husband’s failure to provide maintenance (nafkah) from the perspective of Indonesian Marriage Law and Islamic family law. Marriage in both national and Islamic legal systems aims to establish a harmonious family characterized by tranquility (sakinah), affection (mawaddah), and compassion (raḥmah). However, neglect of maintenance obligations has become one of the dominant causes of divorce cases in Indonesian Religious Courts. This research employs a normative juridical method using statutory and conceptual approaches. The analysis focuses on Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law, and Islamic legal doctrines regarding maintenance obligations and divorce. The study finds that providing maintenance is not only a moral and religious responsibility but also a legal obligation of the husband. Failure to fulfill this obligation continuously may serve as a legitimate legal basis for a wife to file for divorce before the Religious Court. The research further demonstrates that neglecting maintenance constitutes a violation of the wife’s civil rights and contradicts the fundamental objectives of marriage under both Indonesian law and Islamic legal principles. The novelty of this study lies in its integrative analysis combining national marriage law, Islamic family law, and the concept of civil liability (wanprestasi) within marital relations. This study contributes to strengthening legal protection for wives and emphasizes the importance of enforcing maintenance obligations to preserve justice and harmony in family life.